Families of special Weierstrass points - Gatto, Letterio; Salehyan, Parham [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2009)
The purpose of this Note is to show that loci of (special) Weierstrass points on the fibers of a family pi: X -> S of smooth curves of genus g >= 2 can be studied by simply pulling back the Schubert calculus naturally living on a suitable Grassmann bundle over X. Using Such an idea we prove new results regarding the decomposition in A(*)(X) of the class of the locus of Weierstrass points having weight at least 3 as the SLIM of classes of Weierstrass points having "bounded from below" gaps sequences. To cite this article: L. Gatto, P Salehyan, C R. Acad. Sci. Paris, Ser. I 347 (2009). (C) 2009 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.